Efficiency and effectiveness of marketing in Kuala Lumpur's hotels - Rahmati, Elham; Abdul Jalil, Suhaila (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This study employs the two separate data envelopment analysis model to measure marketing efficiency and marketing effectiveness of three- to five-star hotels in Kuala Lumpur during the years 2004-2010. The efficiency and effectiveness calculated show that a high performance in marketing efficiency does not necessarily ensure high profitability. Through star ranking analysis, this study shows that the average marketing efficiency of the hotels increased with lowering star ranking due to heightened demand of agglomeration. In contrast, marketing effectiveness of the hotels decreased with lowering star ranking due to two important factors: economies of scale and room rates.